Fiscal Policies and Subnational Economic Growth in Mexico - Srithongrung, Arwiphawee; Sánchez-Juárez, Isaac (International Journal of Economics and Financial Issues, 2014)
This study investigates the effects of taxes and public investment on economic growth of Mexican states. The subnational government finance data were drawn from 32 states during the period of 1993 to 2011. Correcting for long-term trends and isolating cointegration effects between economic growth and public finance, the empirical results indicate that taxes have negative effect on growth and the effect can be seen in both transitory and permanent manners. As predicted by growth theory, the effects of public investment on subnational growth are statistically significant and positive in both short and long-runs. On the other hand, we find that educational accomplishment positively relates to growth; but only in the long-run. Foreign direct investment does not have any significant effect on subnational economic growth. In general, the results imply that an appropriate fiscal policy (equilibrium between public investment and taxes) is required to boost economic growth in this country. Keywords: Mexico; economic growth; taxes; public investment; states. JEL Classifications: O11; O23; O47; R11.